2019
DOI: 10.1007/s12298-019-00714-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the genetic basis of nitrogen use efficiency in wild and cultivated barley

Abstract: To curb the increasing demand for nitrogenous fertilizers, it is imperative to develop new cultivars with comparatively greater nitrogen use efficiency (NUE). Nonetheless, so far very meager information is available concerning the variances among barley (Hordeum vulgare L.) varieties for their response to nitrogen deprivation. The current study was carried out to explore the potential of barley genotypes for higher NUE. A hydroponic experiment was conducted at seedling stage to compare the performance of four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…The NRT2 gene family has also been reported in model crop species, including tobacco [44], M. truncatula [45], tomato [34] and soybean [46], and also in cereal/grass crop species, including barley [38], rice (Oryza sativa) [47], maize [48], sorghum [49] and Brachypodium [50]. Phylogenetic analysis demonstrated that the NRT2 genes of grass and cereals positioned distantly from that of A. thaliana, which make it hard to predict the function of those genes in grass and cereals based on functional characterisation in A. thaliana [13].…”
Section: Nitrogen Transportation Capacitymentioning
confidence: 98%
See 1 more Smart Citation
“…The NRT2 gene family has also been reported in model crop species, including tobacco [44], M. truncatula [45], tomato [34] and soybean [46], and also in cereal/grass crop species, including barley [38], rice (Oryza sativa) [47], maize [48], sorghum [49] and Brachypodium [50]. Phylogenetic analysis demonstrated that the NRT2 genes of grass and cereals positioned distantly from that of A. thaliana, which make it hard to predict the function of those genes in grass and cereals based on functional characterisation in A. thaliana [13].…”
Section: Nitrogen Transportation Capacitymentioning
confidence: 98%
“…The pioneer investigations on NRT1 was conducted with A. thaliana due to the ease of obtaining mutants and transgenic plants [33]. However, close homologues of the A. thaliana NRT1 gene have been identified in other species such as tomato [34] and M. truncatula [35] and in cereals including rice [36], sugarcane [37], barley [38], maize [39], and wheat [40]. Until now, the functional characterization of this gene family has not been conducted in many crop species including wheat.…”
Section: Nitrogen Transportation Capacitymentioning
confidence: 99%
“…Nitrogen use efficiency (NUE) is increasingly important (Ekardt et al, 2018). Studies with wild barley suggest that it inherits improved NUE and could be a valuable source for new alleles (Shah et al, 2017(Shah et al, , 2019Zahn et al, 2020). Rehman et al (2021) screened wild barley accessions and found several accessions that were less susceptible to common diseases (net blotch, scald, leaf rust and powdery mildew).…”
Section: Wild Barley: a Highly Resilient Subspeciesmentioning
confidence: 99%
“…Phenotyping technologies may be used to screen CWR directly, followed by crossing of the CWR with a cultivar with a suitable genetic background and then selection, or conversely, CWR may be crossed with domesticated lines first, followed by evaluation of the F 1 ; both strategies involve advancement and screening of multiple subsequent backcross generations (Dempewolf et al, 2017;Zhang et al, 2022). Identification of the specific genes or quantitative trait loci (QTL) conferring resistance or tolerance to the target trait(s) can speed up the process of ensuring relevant genes are introgressed through markerassisted selection (Swamy and Sarla, 2008;Sharma et al, 2013;Migicovsky and Myles, 2017). There are some examples where this type of pre-breeding work has paid dividends.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, plant genetic information is also an important approach to improve NUE [ 15 ]. For instance, Shah et al [ 16 ] reported that the NRT2.1 expression level in the N-efficient genotypes was higher than that in the inefficient ones in barley under low-N stress. Likewise, Wei et al [ 17 ] found that overexpression of TaGS2 may improve nitrogen assimilation under N-deficit conditions.…”
Section: Introductionmentioning
confidence: 99%